PERANCANGAN SIKAT PEMBERSIH BABAT SAPI UNTUK MENINGKATKAN KENYAMANAN PEKERJA - Firman Ardiansyah Ekoanindiyo; Antoni Yohanes; Endro Prihastono (Sekolah Tinggi Teknologi Industri Padang, 2022)
In the daily food that we eat in addition to protein, vitamins, animal needs are also needed. Animal needs that we need is beef. Beef processing has several kinds of activities, including the process of cutting meat, cutting of beef tripe offal, boiling tripe dapi, cleaning beef tripe, weighing and then the last process is distribution to consumers. In interviews conducted with workers in beef processing, it was found that one of the most tiring processes and made hands hurt. In washing and cleaning dirt using this knife, it takes a long time so that workers' hands are sometimes injured and their hands feel tired or sore. The subjects measured to obtain anthropometric measurement data were 30 workers related to the processing and cleaning of beef tripe innards at the Wonodri market, Semarang. Anthropometric data used are Palm Thickness to Thumb, Palm Width, Palm Length. From the results of the Nordic Body Map questionnaire, all 30 workers felt pain in the right wrist and pain in the right hand. With the new beef tripe cleaning brush, it does not hurt the hands of workers and reduces pain and soreness in the right wrist and right hand. The cleaning time of beef tripe is faster and more efficient than the previous tool. Cow tripe traders in Wonodri market can reduce production time and increase the comfort of workers in cleaning beef tripe.